The promotion of rainwater harvesting as a supplementary source of domestic water in Kigali, Rwanda- A feasibility study - Sully, Robert Peter (My University, 2007)
Theme and Context Despite being the source of two of Africa’s greatest rivers, the Nile and the Congo, Rwanda is a water scarce country and 50% of the citizens of the capital, Kigali, do not have access to safe drinking water. Rwanda’s tragic history of violent social upheaval combined with regional macro-economic factors and the effects of globalization have made this tiny country one of the poorest on the African continent. Aim and Objectives of this Study The aim of this report is to establish the value that Rainwater Harvesting holds as a supplementary water source for the city of. To evaluate this potential intervention, the suitability of the climate for the harvesting of rainwater is reviewed as well as the availability of the required resources and the effect that the prevailing social environment may have on an implementation program. The current developments in the practice of Rainwater Harvesting are researched and ways in which Rainwater Harvesting could be utilized are explored as well as the possible impediments that might be encountered. Scope and Methodology Adopted The scope of the report includes: 1. Providing an overview of the country both geographically as well as socially. 2. Establishing the need for alternative water sources by: a. Reviewing the present water supplies for the city particularly with regard to their vulnerability to the rapid environmental degradation being experienced within the country, b. Reviewing the prevailing water/health nexus. 3. Investigating metrological records, specifically rainfall patterns, and the quality of the statistics. 4. Review international trends and research in rainwater harvesting specifically in poor countries. 5. Considering obstacles to implementing a wide-ranging scheme to harvest rainwater. The methodology adopted includes: 1. Reviewing published research on the subject of Rainwater Harvesting techniques and implementation. 2. Attending symposia on the subject. 3. Meeting with water practitioners both in the public sector as well as in NGOs to establish the current status of water availability, quality and consumption. 4. Conducting on-site research into water sourcing problems in and around Kigali. 5. Designing, sizing and costing hypothetical installations suitable for local conditions. Summary of Main Findings, Conclusions and Recommendations Although the climate and topography are very favorable to the use of Rainwater Harvesting, this report finds that the promotion of Rainwater harvesting is just one of a number of possible interventions which should be pursued in order to improve the availability of water to the citizens of Kigali The cost and sophistication of Rainwater Harvesting schemes vary considerably but at the lower end of the scale the technology would be affordable to most Kigali residents and the community has the potential human resource to be trained to execute the work. Obstacles to this approach include ignorance about the safety of storing water, the comparative low cost of municipal water the perception that water collection is the responsibility of a family’s women and children. This report also found that a household using a Rainwater Harvesting scheme is likely to require some supplementary water on occasions. Furthermore, as the potential to catch sufficient water is a function of the ratio of a dwelling’s roof area to the number of inhabitants, its efficacy is limited in densely inhabited poor communities. Strong leadership and coordination would be necessary for a successful wideranging Rainwater Harvesting implementation project. In addition a coordinated educational programme will have to be conducted to dispel myths about stored water and to create the required skills base. The statutes and bylaws regarding water would also have to be reviewed to avoid legal impediments. This report concludes that rainwater harvesting cannot be relied upon to fulfill all the communities’ water needs but it can go a long way to improving the general access to safe water and in so doing reduce the time and labour presently demanded, mainly of women and children, in the carrying of heavy loads of water.
Student Number : 7336898 - MSc (Eng) research report - School of Civil and Environmental Engineering - Faculty of Engineering and the Built Environment
Keywords: water supply; rainwater harvesting; Rwanda